A cross‐sectional assessment of frailty, falls and perceptions of ageing in people living with HIV using an mHealth platform. Issue 4 (25th September 2022) - Levett, Tom J.; Vera, Jaime H.; Jones, Christopher I.; Bremner, Stephen; Leon, Agathe; Begovac, Josip; Apers, Ludwig; Borges, Margarida; Zekan, Sime; Teofilo, Eugenio; Garcia, Felipe; Whetham, Jennifer; et al.
Abstract: Objective: To evaluate frailty, falls and perceptions of ageing among clinically stable individuals with HIV, engaged with remote healthcare delivered via a novel smartphone application. Methods: This was a multi‐centre European c ross‐sectional, questionnaire‐based sub‐study of EmERGE participants. Frailty was assessed using the five‐item FRAIL scale. Present criteria were summed and categorized as follows: 0,  robust; 1–2,  pre‐frail; 3–5,  frail. Falls history and EQ‐5D‐5L quality of life measure were completed. Participants were asked their felt age and personal satisfaction with ageing. Results: A total of 1373 participated, with a mean age of 45 (± 9.8) years. Frailty was uncommon at 2%; 12.4% fell in the previous year, 58.8% of these recurrently. Mood symptoms and pain were prevalent, at 43.3% and 31.8%, respectively. Ageing satisfaction was high at 76.4%, with 74.6% feeling younger than their chronological age; the mean felt age was 39.3 years. In multivariable analysis, mood symptoms and pain were positively associated with frailty, falls and ageing dissatisfaction. An increase in pain severity and mood symptoms were respectively associated with 34% and 63% increased odds of pre‐frailty/frailty. An increment in pain symptoms was associated with a 71% increase in odds of falling. Pain was associated with ageing poorly, as were mood symptoms, with odds of dissatisfaction increasing by 34% per increment in severity. Conclusions: Although uncommon, frailty, falls and ageing dissatisfaction were seen in a younger cohort with medically stable HIV infection using a remote care model, promoting screening as advocated by European guidelines. These were more common in those with pain or mood symptoms, which should be proactively managed in clinical care and explored further in future research.